Transradial and transulnar access for iliac artery interventions using sheathless guiding systems: A feasibility study. Issue 6 (3rd June 2016) - Ruzsa, Z.; Tóth, K.; Nemes, B.; Édes, I.F.; Nardai, S.; Berta, B.; Kovács, N.; Hüttl, K.; Merkely, B.
Abstract : Purpose: Our aim was to evaluate the acute success and complication rates of the transradial and transulnar access for iliac artery stenting using sheathless guiding systems. Methods: Clinical and angiographic data from 156 consecutive patients with symptomatic iliac artery stenosis who were treated with transradial or transulnar access were evaluated. All patients underwent Duplex ultrasound before and after the intervention. The primary endpoints were the procedural success rate, major adverse events, and access site complication rates. The secondary endpoints were the angiographic result of the iliac artery intervention, fluoroscopy time, X‐ray dose, procedure length, crossover rate to another puncture site and hospitalization duration. The impact of the learning curve was also investigated, along with right or left radial access. Results: The indication for the intervention was intermittent claudication in 109 patients (69.9%), critical limb ischemia in 44 (28.2%) subjects and acute limb ischemia in three individuals (1.9%). Technical success was achieved in 155 patients (99.4%), with a crossover rate of 3.8%. Radial and ulnar artery access was used in 151 (96.8%) and 7 (4.5%) patients, respectively. The Ankle‐brachial index increased from 0.69 [0.65–0.72] to 0.91 [0.88–0.95] as a result of the procedures ( P < 0.001). The cumulative incidence of major adverse events was 3.8% at the 2‐month follow‐up (0% in patients with intermittent claudication and 13.8% in patients with critical limb ischemia). Radial artery access site complications were encountered in eight patients (5.1%). We documented decreased X‐ray doses (1742.0 [783.9–2701] vs. 1435 [991.1–1879] vs. 692.8 [275.3–1110] Gy cm −2 P < 0.05) over time; however, the fluoroscopy time, procedure time, and contrast consumption were not significantly different. Left hand access was not associated with significantly better results than right radial artery access. Conclusions: Iliac artery stenting can be safely and effectively performed using radial or ulnar artery access and sheathless guiding catheters, with acceptable complication rates and high levels of technical success. The physician learning curve plays an important role in decreasing the X‐ray dose. © 2016 The Authors. Catheterization and Cardiovascular Interventions Published by Wiley Periodicals, Inc.